KAJIAN PSIKOLOGI SASTRA TENTANG AGRESIVITAS TOKOH UTAMA DALAM NOVEL REMBULAN TENGGELAM DI WAJAHMU KARYA TERE-LIYE - Kurnianingsih, Ari; Martono, Martono; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this research is to describe the form, dimension as well as the plan to use the novel Rembulan Tenggelam di Wajahmu works of Tere Liye in school learning. The research is conducted through descriptive method in the form of qualitative. Based on the data analysis (1) the form of aggressive behaviour of the main character  are: physical aggressive (including hitting, kicking, pushing, and strangling) and verbal aggressive (including swearing, saucing, shouting, and snapping). (2) The dimension of aggressive behaviour of the main character are including direct active physical aggressive (including forcibly opening the box, hitting, punching, kicking, piercing, atc. which is done directly by the aggressor), direct active verbal aggressive behaviour (including  snapping, seolding, etc. which is done directly by the aggressor), and indirect active verbal aggressive behaviour (including swearing without the knowledge  of sufferer, soucing to the heart, cursing, etc. which is done by the indirectly by the aggressor). (3) Seen from curriculum aspect, learning objectives aspect, teaching material selection aspect, and readable aspect shows that this novel can be implemented in school learning especially for Bahasa Indonesia subject. Keywords: Novel, Aggressive, Behavioristic Psychology